Działania ukierunkowane na osiągnięcie sukcesu życiowego podopiecznych SOS Wioski Dziecięcej - Reterska-Tkaczyk, Sandra (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The article presents the role of a foster family in meeting basic and psychological needs of a teenager, shaping their cognitive, emotional and social needs, and equipping them with a certain system of values, social norms as well as attributes necessary to succeed in adult life. The activities of the SOS Children’s Village of the Youth Housing Community in Koszalin are the subject matter of the article. These activities aim to raise the charges’ self-acceptance and self-esteem as well as assist in accomplishing their objectives and reaching maturity. Furthermore, the activities focus on strengthening the qualities, namely perseverance and teamwork, which determine consistent achievement of life goals. Another aim of the activities is helping the teens to confront the real world through experience. The article concerns psychological, pedagogicand medical assistance, motivation in education, development of passions andinterests, a well as individual sessions with educators and specialists. It also deals with overcoming learned helplessness, and involving the charges in both seasonal work and volunteering. Finally, the article presents the implementation of housingprograms for those who have already left the institution.
Keywords: poczucie wartości; podopieczni; rodzina; SOS Wioski Dziecięce; sukces życiowy; teoria wyuczonej bezradności; wychowankowie